Adoption of social networking sites (SNS) among private college educators in Kota Kinabalu : application of unified technology acceptance and use of technology (UTAUT) model - Ramesh Salimun (2014)
Social networking sites (SNS) have become very popular in recent years, and its adoption has skyrocketed. Following this trend among the general public, educators are also increasingly adopting these tools for their professional work. However, currently, there is no research to explore educators' adoption of SNS in private college in Kata Kinabalu. The current study seeks to investigate educators' acceptance and adoption of SNS for communication and information dissemination in the area of teaching in private colleges in Kata Kinabalu. To achieve this, the paper uses an amended Unified Theory of Acceptance and Use of Technology (UTAUT), a widely adopted technology acceptance theory. Four independent variables were used to examine the behavioral intention to use SNS among the private college educators. They are; Performance expectancy, effort expectancy, social influence and facilitating conditions. Gender was used to moderate the relationship between the independent variables and dependent variables (behavioral intention). The four constructs were operationalized to develop the questionnaires which were distributed to educators in eight private colleges in Kata Kinabalu. 200 questionnaires were obtained from the selected eight colleges. The data from 200 educators show that performance expectancy, effort expectancy and social influence have significance influence to adopt SNS among the private college educators. The correlation values shown were quite significant and it indicates that the model can be used as a tool to investigate SNS adoption among private college educators in Kota Kinabalu.